Enhanced Parallel Hash Function Algorithm Based on 3C Construction (EPHFA-3C) - Abdelfatah, Roayat Ismail; Abdelkhalek B, Esraa; E. Nasr , M. (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
The hash function is a function that can convert data from variable size to fixed-size data that can be used in security of communication like, authentication, digital signature and integration. In this paper, a parallel, secure and fast hash function algorithm that is based on 3C construction is proposed. It is an enhancement for the MD construction. This enhancement makes the construction more resistant to the extension and multi-blocks attacks. The parallel structure of the algorithm improves the speed of hashing and reduces the number of operations. The simulation analysis such as hashes distribution, confusion and diffusion properties, and collision resistance are executed. Based on the results, our proposed hash algorithm is efficient, simple, and has strong security compared with some recent hash algorithms.